Relationship between the Divine Law and Policy in the Transcendental Theosophy - Sharif Lakzaei (حکمت اسرا, 2012)
This article tries to explain the relationship between the divine law and policy in the transcendentaltheosophy and also the four distinctions (difference in Origin, difference in Final Goal, difference in actions, and difference in passivity) of these two views of Mulla Sadra will be discussed. Paying attention to the analysis regarding the relationship between the body and soul is an innovation. In this paper as Mulla Sadra specifies, the relationship between the divine law and policy has been analyzed from the perspective of the relationship between the body and soul. In addition, this argument has been considered in terms of the theory of “substantial motion”. What is prominent in the Mulla Sadra's discussions is that he believes that the ultimate goal of the policy is to empower the divine law. So from this perspective, we can say that the policy prepares the ground for empowering divine law, which has been discussed in detail in this paper emphasizing on the relationship between the body and soul; and between the divine law and policy.